Heterogeneous catalysis for valorisation of vegetable oils via metathesis reactions: Ethenolysis of methyl oleate - Nieres, Pablo Daniel (2016)
The cross-metathesis of methyl oleate (MO) with ethylene was studied on a second-generation Hoveyda?Grubbs complex supported on silica (HG/SiO2). The reaction was carried out in a batch slurry reactor at 313?353 K and 2.5?7.5 bar of C2H4(5%)/N2, using cyclohexane as a solvent. The MO ethenolysis productswere methyl 9-decenoate and 1-decene. The competitive MO self-metathesis reaction formed 9-octadecene and methyl 9-octadecen-1,18-dioate. The yield (YE) and selectivity (SE) for ethenolysis products at PC2H4 = 0.125 bar (total pressure = 2.5 bar) were 52% and 69%, respectively. Both parameters increasedwith PC2H4, essentially because the reaction equilibrium was shifted to higher methyl oleate conversions. Thus, at PC2H4 = 0.250 bar, the YE and SE values were 63% and 77%, respectively. Nevertheless, catalyst deactivation was observed for ethylene pressures higher than 0.125 bar, thereby suggesting that the presence of ethylene may suppress the metathesis cycle on HG/SiO2 catalysts. The ethenolysis product yield decreased when the temperature was increased, reflecting mainly the MO equilibrium conversion diminution.